Social Networking and Adolescents’ Behavioural Problems (Drug abuse, Bullying and Cultism) in Uyo Local Government Area, Akwa Ibom State, Nigeria - Ekot, Mildred; Umoh, E. I. (Advances in Social Sciences Research Journal, 2020)
The study aimed at investigating the influence of social networking on adolescents’ behavioural problems (Drug abuse, bullying and cultism) in Uyo Local Government Area of Akwa Ibom State. The study adopted the descriptive survey research design. The population for the study was 14,739 from 14 public secondary schools in the study area, and a sample size of 601 students was selected through a multi-stage sampling technique. The instrument used for data collection was a structured questionnaire developed by the researchers. Data obtained were analysed using Mean and simple regression analysis. Results showed that Facebook was the most frequently used social networking site. Findings also revealed that social networking had significant influence on drug abuse (P<.05) and cultism (P<.05), but the influence on bullying tendency was not significant (P>.05). On the basis of the findings, it was recommended among others, that individuals, groups, civil societies and the government should continue to sensitize the public on the dangers of all anti-social behaviours through social networking sites to help reduce their rate of involvement. Further studies was also recommended to explore the influence of social networking on a non-student adolescent population or out of school adolescents.